Cultural intelligence in multicultural teams : a systematic literature review - Torkko, Mirella (2020)
Since the number of cross-cultural encounters in the modern working society is growing. It has become important to knowledge one’s own course of action in multicultural environment. People who work naturally well in cross-cultural situations are called culturally intelligent. These people can rapidly change their behavior and adapt to the multicultural environment. This capability is called cultural intelligence (CQ). Cultural intelligence becomes especially important when people from varying cultural backgrounds work together in teams.